Finance and diversification - Simone Manganelli; Alexander Popov (European Central Bank (ECB), 2010)
We study how financial market efficiency affects a measure of diversification of output across industrial sectors borrowed from the portfolio allocation literature. Using data on sector-level value added for a wide cross section of countries and for various levels of disaggregation, we construct a benchmark measure of diversification as the set of allocations of aggregate output across industrial sectors which minimize the economy's long-term volatility for a given level of long-term growth. We find that financial markets increase substantially the speed with which the observed sectoral allocation of output converges towards the optimally diversified benchmark. Convergence to the optimal shares of aggregate output is relatively faster for sectors that have a higher "natural" long-term risk-adjusted growth and which exhibit higher information frictions. Our results are robust to using various proxies for financial development, to accounting for the endogeneity of finance, and to controlling for investor's protection, contract enforcement, and barriers to entry. Crucially, the observed patterns disappear when we employ "naive" measures of diversification based on the equal spreading of output across sectors.
Keywords: E32; E44; G11; O16; 330; diversification; Financial Development; Growth; Mean-variance efficiency; Volatility; Finanzmarkt; Effizienzmarkthypothese; Diversifikation; Wirtschaftswachstum; Volatilität; OECD-Staaten